Effect of mutant variants of the KRAS gene on PD-L1 expression and on the immune microenvironment and association with clinical outcome in lung adenocarcinoma patients. (July 2018) - Falk, Alexander T.; Yazbeck, Nathalie; Guibert, Nicolas; Chamorey, Emmanuel; Paquet, Agnès; Ribeyre, Lydia; Bence, Coraline; Zahaf, Katia; Leroy, Sylvie; Marquette, Charles-Hugo; Cohen, Charlotte; Mograbi, Baharia; et al.
Abstract: Objectives: The effect of anti-PD-1/PD-L1 inhibitors on lung adenocarcinomas (LADCs) with KRAS mutations is debatable. We examined the association between specific mutant KRAS proteins and the immune infiltrates with the outcome of patients with LADCs. Patients and methods: In 219 LADCs harboring either wild-type (WT) or mutated KRAS gene, we quantified the density of several immune markers by immunohistochemistry followed by automated digital image analysis. Data were correlated to clinicopathological parameters and outcome of patients. Results: Tumors harboring mutant KRAS -G12 V had a significantly higher PD-L1 expression compared to other tumors ( p  = 0.044), while mutant KRAS -G12D tumors showed an increase in the density of CD66b+ cells ( p  = 0.001). High PD-L1 expression in tumor cells was associated to improved overall survival (OS) in KRAS mutant patients ( p  = 0.012), but not in the WT population ( p  = 0.385), whereas increased PD-L1 expression in immune cells correlated to poor OS of KRAS -WT patients ( p  = 0.025), with no difference in patients with KRAS mutations. Conclusions: KRAS mutational status can affect the immune microenvironment and survival of LADC patients in a heterogeneous way, implying that specific mutant KRAS variants expressed by the tumor should be considered when stratifying patients for immunotherapy.